Relationship between grain yield of soybeans and meteorological variables - Berlato, Moacir A.; Fontana, Denise Cybis; Gonçalvez, Hélio M. (Pesquisa Agropecuaria Brasileira, 1992)
The objective of this study was to estimate correlations between original and derivated meteorological variables and grain yield of soybeans during different plant growth periods. Data used for this analysis were originated from experiments conducted in five locations of Rio Grande do Sul State, Brazil, from 1971/72 to 1983/84. The results show that, for the recommendable sowing period, temperature is not a limitative factor for soybean grain yield in the most important croping areas of the State. The original variable rainfall was highly correlated with grain yield only during the reproductive period. Derivated variables (P/ETo and ET/ETo) were better related with grain yield as compared to rainfall either for vegetative or reproductive periods. The ET/ETo index exhibited the best correlations with grain yield. As a consequence, it is the most indicated variables to be used in models involving climate-soybean grain yield relationships. The results also show that reproductive period is the most critical to water deficit. This period usually occurs from mid January to mid March for all three maturity groups in Rio Grande do Sul.